Análise dos indicadores da osteogênese, citotoxicidade e genotoxicidade de substitutos ósseos em osteoblastos-like - Milhan, Noala Vicensoto Moreira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to investigate in vitro the indicators of osteogenesis, the cytotoxicity and genotoxicity of osteoblast-like (MG 63) in indirect contact with three bone substitutes: Hydroxypatite Bovine (HA) (Bio -Oss ® - Geistlich), Beta Tricalcium Phosphate (β -TCP - Bionnovation) and experimental Beta Tricalcium Phosphate (β -TCP experimental). The osteoblasts-like were exposed to the materials for 24 h, through the use of conditioned medium by bone substitutes in the concentration of 16 mg/mL. The indicators of osteogenesis were analyzed by alkaline phosphatase activity, total protein content and formation of mineralized nodules. Cell viability was measured by MTT assay and genotoxicity was determined by the formation of micronuclei (MNT) in the cells after exposure to the bone substitute and also to the etilmetano sulfanato (positive control). The data obtained were submitted to ANOVA, Tukey's multiple comparison (Post Hoc) and Z test (p < 0,05 ). The MTT assay showed that none of the tested materials was cytotoxic. Furthemore, the β -TCP, followed by Bio- Oss® , induced proliferation of cells after 24 h. The MNT test indicated that none of the bone substitutes was genotoxic. Concerning the indicators of osteogenesis, it was observed that cells in contact with the materials were able to induce osteogenesis and that this process was influenced by the period of culture of osteoblast-like in contact with bone substitutes. The total protein content was the highest in general on the 10th day, while the alkaline phosphatase activity was the highest in all the materials on the 14th day, similar to the formation of mineralized nodules, which also showed the highest values on the 14th day. Among the evaluated bone substitutes, it was found that the β-TCP induced higher osteogenesis than others on all the tests. Based on the results of this study, it was concluded that all.....

O objetivo deste estudo foi investigar in vitro os indicadores osteogênese, a citotoxicidade e genotoxicidade de osteoblastos-like (MG 63) em contato indireto com três substitutos ósseos: Hidroxipatita bovina (HA) (Bio-Oss®- Geistlich), Beta fosfato tricálcico (β-TCP - Bionnovation) e Beta fosfato tricálcico experimental (β-TCP experimental). Os osteoblastos-like foram expostos aos materiais por 24 h, por meio da utilização de meio condicionado pelos substitutos ósseos na concentração de 16 mg/mL. Os indicadores da osteogênese foram analisados pelos testes atividade de fosfatase alcalina, conteúdo de proteína total e formação de nódulos de mineralização. A viabilidade celular foi mensurada pelo teste de MTT e a genotoxicidade foi determinada pela formação de micronúcleos (MNT) nas células após exposição aos substitutos ósseos e também ao etilmetano sulfanato (controle positivo). Os dados obtidos foram submetidos aos testes estatísticos ANOVA, comparação múltipla de Tukey (Post Hoc) e teste Z (p<0,05). Pelo teste de MTT observou-se que nenhum dos materiais avaliados foi citotóxico, sendo que o β -TCP, seguido pelo Bio-Oss®, induziram proliferação celular após 24 h. O ensaio de MNT indicou que nenhum dos substitutos ósseos apresentou genotoxicidade. Em relação aos indicadores da osteogênese, foi observado que as células em contato com os materiais foram capazes de induzir a osteogênese e que esse processo foi influenciado pelo período de cultura dos osteoblastos-like em contato com os substitutos ósseos. O conteúdo de proteína total apresentou-se maior em geral aos 10 dias, enquanto a atividade de fosfatase alcalina foi superior em todos os materiais aos 14 dias, semelhante à formação de nódulos de mineralização, que também apresentou pico de formação no período de 14 dias. Dentre os substitutos ósseos avaliados, foi constatado que ...
Keywords: Hidroxiapatita; Fosfatos; Osteoblastos; Citotoxicidade